Interregional Migration, Human Capital Externalities and Unemployment Dynamics: Evidence from Italian Provinces - Roberto Basile; Alessandro Girardi; Marianna Mantuano; Giuseppe Russo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We analyze the effect of interregional migration on regional unemployment in Italy. With the help of a simple two-region model adapted to the main features of the Italian NorthSouth dualism, we illustrate the effects of labor mobility with and without human capital externalities. Using longitudinal data over the years 2002-2011 for 103 NUTS-3 Italian regions, we document that net outflows of human capital from the South to the North have increased the unemployment rate in the South, while it did not affect the unemployment rate in the North. Our analysis contributes to the literature on interregional human capital mobility suggesting that reducing human capital flight from Southern regions should be a priority.
Keywords: C23; R23; J61; 330; Unemployment; Migration; Human Capital; Exernalities; Italian Regions